A Rewritable, Reprogrammable, Dual Light‐Responsive Polymer Actuator. Issue 43 (22nd September 2017) - Gelebart, Anne Helene; Mulder, Dirk J.; Vantomme, Ghislaine; Schenning, Albertus P. H. J.; Broer, Dirk J.
Abstract: We report on the fabrication of a rewritable and reprogrammable dual‐photoresponsive liquid crystalline‐based actuator containing an azomerocyanine dye that can be locally converted into the hydroxyazopyridinium form by acid treatment. Each dye absorbs at a different wavelength giving access to programmable actuators, the folding of which can be controlled by using different colors of light. The acidic patterning is reversible and allows the erasing and rewriting of patterns in the polymer film, giving access to reusable, adjustable soft actuators. Abstract : Bending patterns : Rewritable and reprogrammable actuators can be obtained by using the local activation of an initially chemically homogenous film. The locally activated material is exposed to UV light, which results in the precise folding of the actuator. By switching the wavelength, a different shape can be obtained. Furthermore, the pattern can be erased and a new one can be written, giving access to a multitude of actuated shapes.